#1**+10 **

pq + 12 = 3p + pr

Subtract pr from both sides

pq - pr + 12 = 3p

Factor the p from the first two terms on the left-hand side

p(q-r) + 12 = 3p

Use the fact that q - r = 7

7p + 12 = 3p

Subtract 3p from both sides

4p + 12 = 0

Subtract 12 from both sides

4p = -12

Divide both sides by 4

p = -3

.

Alan Feb 26, 2015

#1**+10 **

Best Answer

pq + 12 = 3p + pr

Subtract pr from both sides

pq - pr + 12 = 3p

Factor the p from the first two terms on the left-hand side

p(q-r) + 12 = 3p

Use the fact that q - r = 7

7p + 12 = 3p

Subtract 3p from both sides

4p + 12 = 0

Subtract 12 from both sides

4p = -12

Divide both sides by 4

p = -3

.

Alan Feb 26, 2015